Puerto Rican Studies: Changing Islands of Knowledge - Pedro Cabán (Centro Journal, 2009)
This essay discusses the factors that help explain the paradox of Puerto Rican Studies; on one hand the sustained institutional resistance to the establishment of viable Puerto Rican Studies academic units, and on the other, the growing acceptance of Puerto Rican Studies scholarship as a viable contributor to multidisciplinary research and teaching. The essay reviews the context in which Puerto Rican Studies units were established and discusses the array of factors that curtailed their institutional development. It also traces the trajectory of Puerto Rican Studies scholarship. It summarizes the diverse research priorities and competing intellectual currents in the prevailing scholarship. During the last four decades Puerto Rican Studies scholarship has acquired a measure of academic legitimacy and in the process has generated productive scholarly engagements with other disciplines.